Acetabular Re-Revision with Impaction Bone Grafting and a Cemented Polyethylene Cup; A Biological Option for Successive Reconstructions. Issue 1 (January 2015) - Schreurs, B. Willem; te Stroet, Martijn A.J.; Rijnen, Wim H.C.; Gardeniers, Jean W.M.
Introduction: For the revision of failed acetabular components impaction bone grafting (IBG) with a cemented cup is a well known technique. Claims have been made that this is a biological reconstruction technique, restoring the bone stock loss and thereby facilitating future revisions. However, there are no scientific data proving this claim. Patients and Methods: In this study, we present the clinical and radiographic outcome of 11 consecutive acetabular re-revisions in 10 patients with again IBG and a cemented polyethylene cup observed in a previously reported cohort of 62 acetabular IBG revisions. All data were prospectively collected. Kaplan-Meier survivorship analysis was performed. Results: The mean follow-up after re-revision was 10 years (5-15) and 28 years (26-30) after the primary revision. No patients were lost to follow-up. The mean HHS improved from 37 (12-49) points to 71 (40-95) points at final follow-up. Survival with further cup revision for any reason as endpoint was 91% (95% confidence interval (CI) 51 to 99) at 10 years. When excluding one early cup re-revision for malpositioning 3 weeks postoperative, survivorship with further cup revision for aseptic loosening as endpoint was 100% (95% CI 37-100) at 10 years. Survival with further cup re-operation for any reason as endpoint was 82% (95% one-sided CI 45-95). In all surviving re-revisions trabecular incorporation was observed without radiolucent lines. Conclusion: This study shows that, due to restoring the bone stock, even successive acetabular reconstructions using IBG and a cemented cup are possible with satisfying 10 years survivorship.